EVALUASI KINERJA DAN PERBAIKAN KAPASITAS JALAN SUNGAI RAYA DALAM - Mintorogo, Rasto; AS, Syafaruddin; Kadarini, S. Nurlaily (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
Highways are transportation infrastructure that most important for transportation activity. The transportation activity also very influence from growing of the people and increasing of vehicle. As high as level of growing people make level of vehicle also increases that will effect for traffic light problems, as that happened in Jalan Sungai Raya Dalam. This street is border and connection between Pontianak City and Kubu Raya Regency. The highway condition is crowded and not good, This condition cause side friction that make highways capacity is low and highways activity is decreasing. The purpose of this research is calculate of highways activity in 2013 and prediction in 2015 till 2020, then to know representation for fixing capacity planning for increase highways activity. This research, the data got from Statistic Center Department and Traffic Light Police Department. While survey of traffic volume and side friction did on Friday, Saturday, Sunday and Monday (at 6-7 and 12-14 December 2013) from 6 pm – 6 am. Based the survey result will calculate and analyse while get capacity and degree saturation. Degree Saturation Value (DS) that require from Highways Capacity Manual of Indonesia (MKJI) 1997 for town road 0,85 is highways service level indicator and determine highwasy activity. Based on the result of research gained value degree saturation (DS) for in 2013 is 0,757, in 2015 is 0,917 and in 2020 is 1,485. This data show that in 2015 and in 2020 will get the traffic problem, so will give alternative and solution with fixing highways capacity, with do to widening highways geometric 8 m or change of highways type 2/2 UD be 4/2 D. From solution alternatif choosed the best alternatif and solution is changed higways type 2/2 UD be 4/2 D while degree saturation (DS) in 2015 lower 0,309 and 2020 lower 0,501.